Intake of Condensed Tannins (Acacia mearnsii) by Lambs in Confinement and Its Impact on Growth Performance, Rumen Environment, and Meat - Andrei L. R. Brunetto; Ana Luiza F. dos Santos; Isadora Zago; Guilherme L. Deolino; Luisa Nora; Vitor L. Molosse; Rafael V. P. Lago; Aline de C. Machado; Roger Wagner; Jelson N. Nauderer; Bianca F. Bissacotti; Aniela P. Kempka; et al. (Fermentation)
This study determined whether adding condensed tannins to the diet of confined lamb improves performance, metabolism, health, and meat composition and quality. We used 24 Lacaune lambs with an average initial weight of 24.5 ± 0.24 kg. The animals were divided into 12 pens with two animals each. In the treatment group, a black wattle extract was added to the lamb concentrate (2.5 g/kg dry matter), while the control group received only the basal diet (without extract). Black wattle contained 98.6 g/kg of condensed tannin. There was no difference between the performance variables, which included weight gain, feed intake, and feed efficiency. However, the group fed on condensed tannins showed higher carcass yield and a higher percentage of linked intramuscular fat. In meat, a lower proportion of saturated fatty acids combined with higher concentrations of unsaturated fatty acids was observed in lambs of the condensed tannin group. The polyunsaturated fatty acids (PUFA) were no different; however, a higher PUFA/SFA ratio was observed in animals with condensed tannin intake, and a higher proportion of ω6 and ω3 was observed in the meat of these animals. The meat’s protein and ash content did not differ between treatments, as did the meat’s water retention capacity, color, and luminosity. Furthermore, animals that fed on condensed tannins had lower cholesterol levels and higher globulin content. The values of erythrogram variables were lower in lambs that consumed condensed tannins. More significant ruminal bacterial activity was also observed in the group receiving condensed tannins. The antioxidant effect was verified with lower thiobarbituric acid reactive species (TBARS) levels and more significant antioxidant enzyme activity. We conclude that adding condensed tannins improves carcass yield and increases the percentage of fat in the carcass, improving the fatty acid profile, which may be linked to the antioxidant effect, in addition to the health benefits of the consumer of this product.